Effect of Macrolide and Non-Macrolide Therapy on QTc Interval Prolongation in Cardiac Patients with Community-Acquired Pneumonia - Dwi Akbarina Yahya; Pendrik Tandean; Khalid Saleh; Almudai MD; Irawati Djaharuddin; Andi Alfian Zainuddin (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. Azithromycin is a macrolide antibiotic widely used to treat various infectious diseases, such as respiratory infections. Several studies have reported an association between azithromycin and QT interval prolongation. QTc prolongation is one of the causes of the life-threatening arrhythmia torsade de pointes (TdP). Torsade de pointes has been reported in approximately 1 % of patients with QT interval prolongation after exposure to azithromycin.Aim. This study aims to determine the effect of macrolide and non-macrolide regimen therapy on the prolongation of the QTc interval in cardiac patients with community-acquired pneumonia.Materials and Methods. This is a retrospective cohort study of 33 cardiac patients with community-acquired pneumonia who received macrolide and non-macrolide therapy during hospitalization. Serial electrocardiograms were performed on days 1, 3, 5, and pre-discharge to evaluate the QTc interval.Outcomes. In the group of heart disease patients with community-acquired pneumonia who received macrolides, there was a significant prolongation of the QTc interval (p<0.05) in the independent T-test, Mann-Whitney test, and Friedman test. Risk factors of age, female gender, history of hypertension, and diabetes mellitus had a significant effect (p<0.05) in the Friedman test.Conclusions. This study shows that macrolide therapy in heart disease patients with community-acquired pneumonia significantly and consistently prolongs the QTc interval throughout the treatment period compared with non-macrolide therapy. Risk factors include age, female gender, history of hypertension, and diabetes mellitus.